PENGARUH BELANJA DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KOTA PARIAMAN - Habibani, Rhaysya Admmi; Asnil, Asnil; Frinaldi, Aldri; Putri, Nora Eka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Regional expenditure is one of the main fiscal instruments of local governments that plays a crucial role in driving economic development and improving public welfare. Through effective and efficient allocation of public budgets, local governments are expected to strengthen local economic capacity and enhance the performance of productive sectors. This study aims to analyze the effect of regional expenditure on economic growth in Pariaman City during the period 2015–2023. The study employs a quantitative approach using a simple linear regression method, in which the independent variable is total regional expenditure, and the dependent variable is economic growth measured by the growth rate of Gross Regional Domestic Product (GRDP) at constant prices. Data were obtained from the official publications of the Regional Financial Agency (BKD) and the Central Bureau of Statistics (BPS) of Pariaman City. The analysis results show that regional expenditure has a positive and significant influence on economic growth, with a regression coefficient value of 0.312 and a coefficient of determination (R²) of 0.61. This indicates that approximately 61% of the variation in economic growth can be explained by changes in regional expenditure. These findings support Keynesian economic theory, which posits that an increase in government spending can stimulate the expansion of economic activity through the multiplier effect mechanism. Nevertheless, the effectiveness of regional expenditure in Pariaman City remains influenced by the structure of budget allocation, which tends to be dominated by operational spending and delays in the realization of capital expenditures. Therefore, improving the quality of public spending is essential to ensure that every rupiah of the budget spent generates tangible impacts on economic growth and public welfare. This study recommends increasing the proportion of productive capital expenditures, implementing result-based budgeting, and strengthening fiscal accountability as key strategies to reinforce the linkage between local fiscal policy and economic performance in the future. ABSTRAKBelanja daerah merupakan salah satu instrumen fiskal utama pemerintah daerah yang berperan dalam mendorong pembangunan ekonomi dan peningkatan kesejahteraan masyarakat. Melalui alokasi anggaran publik yang efektif dan efisien, pemerintah daerah diharapkan mampu memperkuat kapasitas ekonomi lokal dan meningkatkan kinerja sektor-sektor produktif. Penelitian ini bertujuan untuk menganalisis pengaruh belanja daerah terhadap pertumbuhan ekonomi di Kota Pariaman selama periode 2015–2023. Penelitian ini menggunakan pendekatan kuantitatif dengan metode regresi linier sederhana, di mana variabel independen yang digunakan adalah total belanja daerah dan variabel dependen adalah pertumbuhan ekonomi yang diukur berdasarkan laju Produk Domestik Regional Bruto (PDRB) atas dasar harga konstan. Data diperoleh dari publikasi resmi Badan Keuangan Daerah (BKD) dan Badan Pusat Statistik (BPS) Kota Pariaman. Hasil analisis menunjukkan bahwa belanja daerah berpengaruh positif dan signifikan terhadap pertumbuhan ekonomi, dengan nilai koefisien regresi sebesar 0,312 dan nilai koefisien determinasi (R²) sebesar 0,61. Hal ini berarti bahwa sekitar 61% variasi pertumbuhan ekonomi dapat dijelaskan oleh perubahan belanja daerah. Temuan ini mendukung teori ekonomi Keynesian yang menyatakan bahwa peningkatan pengeluaran pemerintah dapat mendorong ekspansi aktivitas ekonomi melalui mekanisme multiplier effect. Meskipun demikian, efektivitas belanja daerah di Kota Pariaman masih dipengaruhi oleh struktur alokasi anggaran yang cenderung didominasi oleh belanja operasional dan keterlambatan realisasi belanja modal. Oleh karena itu, peningkatan kualitas belanja publik menjadi hal yang sangat penting untuk memastikan setiap rupiah anggaran yang dikeluarkan benar-benar memberikan dampak nyata terhadap pertumbuhan ekonomi dan kesejahteraan masyarakat. Penelitian ini merekomendasikan perlunya peningkatan proporsi belanja modal produktif, perencanaan berbasis hasil (result-based budgeting), serta penguatan akuntabilitas fiskal sebagai strategi untuk memperkuat hubungan antara kebijakan fiskal daerah dan kinerja ekonomi lokal di masa mendatang.